Bent femoral intramedullary nail: a case report and review of the literature - Canton, Gianluca; Haxhaj, Bramir; Fattori, Roberto; Murena, Luigi (Acta Biomedica Atenei Parmensis, 2019)
Intramedullary nailing is considered the gold standard technique for the treatment of femoral shaft fractures. A rare complication of this technique is nail bending after a new trauma. In these cases nail removal might be really challenging. The present paper provides a brief review of surgical techniques purposed in the literature for bent nail removal and describes a clinical case.